Exploring the absence of watchdog journalism in Nigeria broadcast media - Gainaka, Maryam Abdu; AlSagoff, Syed Agil; Ahmad Ghazali, Akmar Hayati (Maya Global Education Society, 2020)
Purpose of the study: The research became necessary to explore the watchdog role of broadcast media in Nigeria. The study was conducted for the purpose of understanding how broadcast media interpret the watchdog function and the reason for its rarity in Nigeria broadcast media. Methodology: The study used the qualitative case study approach. Two broadcast media were purposively selected for the study-FRCN and AIT. Semi-structured face to face interview was used to collect data from ten informants comprising of senior editors and field reporters who were purposively selected for the study. Researchers used thematic analysis for data analysis to interpret and discuss findings. Main findings: The broadcast media perform the watchdog role through reporting of investigations not initiated by them and also through their programs. The absence of watchdog in their media is influenced by the interference of broadcast media owners, enormous economic and commercial pressures on them being a more capital intensive media as well as the failure of broadcast media practitioners to explore the freedom of information Act like their print counterparts do. Application/Implication: The findings offer a reference point for media regulatory bodies to discover broadcast media issues that are useful for making regulations to improve media practice. It contributes to the call for media social responsibility by providing insight into the impediments of fulfilling the media’s social obligation as a watchdog. Novelty/originality: Research in the area of media watchdog role and functions have often focused on audience perceptions and evaluations of print media. This study explored broadcast media and added to the conceptualization of the concept of media as watchdog beyond investigative journalism only.